The microscopic diagnostic signs of some Fabaceae L. genus representatives. Message ІІ. Plant conducting system - O. V. Grechana; A. H. Serbin; A. M. Rudnyk; O. O. Salii (Zaporozhye State Medical University, 2021)
The world plant products market is expanded rapidly and trade in them tends to grow by 15-25 % annually. The number of reports is increased proportionally about accidental contamination or deliberate, economically motivated falsification of plant raw materials. 27 % of the nearly 6.000 herbal preparations that are sold in 37 countries have contained undeclared contaminants, substitutes, or other components, according to the literature. We have conducted a plant conduction system microscopic analysis of the individual members' genus Clover (Trifoliae L.), Fabaceae L. to identify morphoanatomical characteristics. Clover has anti-inflammatory, antiseptic, choleretic, diaphoretic, diuretic, hemostatic, expectorant, astringent properties and is used in many diseases. Aim. The finding common features and those that differ and can be used as diagnostic during studying the conducting system structure of genus Trifolium L. leaves and stems. Materials and methods. Plant material (herb) from Trifolium pratense L., T. incarnatum L., T. repens L. and T. fragiferum L. was harvested during the active flowering period - (May - June) and was dried in a well-ventilated place. Leaves and stems preparations were pre-boiled in 5 % sodium hydroxide water solution and fixed in chloral hydrate solution. Cross-sections were made with a microtome. The BIOLAM LOMO light microscope (Russia) and OLYMPUS SH-21 digital camera were used to record the data about identify the conducting apparatus of the plant's leaf, petiole, and stem. Results. It has been examined the central vein structure of T. pratense L. and T. fragiferum L. leaves, it was determined that the conductive system is covered with a crystalline coating and there is one closed collateral bundle in the center, which is not typical for dicotyledonous plants. The petioles of T. incarnatum L., T. fragiferum L., and T. repens L. in cross-section are several different shapes. There are kidney-shaped and round. The conducting apparatus T. incarnatum L. and T. repens L. have arranged in a circle, closed and collateral. The leafstalk structure type of T. fragiferum L. is bunchles. It contradicts too the information about the structure conducting system of dicotyledonous plants. The stem's conducting bundles are collateral and open. Conclusions. We have paid attention to the structural peculiarities of the conductive system of the central vein and petiole of objects for study: Trifolium pratense L., T. incarnatum L., T. repens L., and T. fragiferum L. when searching for differentiating features in some members of the genus Trifoliae L. in pharmacognostic analysis. The Dicotyledonae representatives are not characteristic of the closed type of conductive bundles, which we observed during microscopic examination.